BS EN 60287-1-3. Electric cables. Calculation of the current rating. Part 1-3. Current rating equations (100 % load factor) and calculation of losses. Current sharing between parallel single-core cables and calculation of circulating current losses (19th February 2021) - British Standards Institution,
No abstract available